2015
DOI: 10.3332/ecancer.2015.591
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing brain cancer: what physicians should know about patients

Abstract: During the last 20 years, numerous studies have highlighted the need to consider Quality of Life (QoL) issues in the treatment of brain cancer. However, gaps in scientific knowledge are still present as we have poor data surrounding the whole experience in patients and regarding their needs.The present study was aimed at evaluating QoL in brain cancer patients and correlated aspects. In particular, we aimed to assess QoL, mood state, and emotional issues in order to describe the patients’ experience to find ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The NEQ was originally designed and validated by Tamburini et al at the Psychology Unit of Instituto Nazionale Tumori in Italy [8,30,31]. In the PUBMED database, there were 14 studies conducted using the NEQ [8,15,[30][31][32][33][34][35][36][37][38][39][40][41]. Validation of the NEQ as a clinical tool for identifying the needs of hospitalized cancer patients was performed [8,30,31,35], and the contributions concluded that using the NEQ is functional, of value, and to be recommended.…”
Section: Selection Of An Instrument To Assess the Needs Of Polish Can...mentioning
confidence: 99%
“…The NEQ was originally designed and validated by Tamburini et al at the Psychology Unit of Instituto Nazionale Tumori in Italy [8,30,31]. In the PUBMED database, there were 14 studies conducted using the NEQ [8,15,[30][31][32][33][34][35][36][37][38][39][40][41]. Validation of the NEQ as a clinical tool for identifying the needs of hospitalized cancer patients was performed [8,30,31,35], and the contributions concluded that using the NEQ is functional, of value, and to be recommended.…”
Section: Selection Of An Instrument To Assess the Needs Of Polish Can...mentioning
confidence: 99%